2021
DOI: 10.3389/fphys.2021.767439
|View full text |Cite
|
Sign up to set email alerts
|

Redox Properties of Human Erythrocytes Are Adapted for Vitamin C Recycling

Abstract: Ascorbic acid (AA; or vitamin C) is an important physiological antioxidant and radical scavenger. Some mammalian species, including homo sapiens, have lost the ability to synthetize AA and depend on its nutritional uptake. Erythrocytes from AA-auxotroph mammals express high amounts of the glucose transporter GLUT1. This isoform enables rapid uptake of glucose as well as dehydroascorbate (DHA), the fully oxidized form of AA. Here, we explored the effects of DHA uptake on the redox metabolism of human erythrocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…DHA is an unstable molecule that can be rapidly degraded irreversibly both inside and outside cells [ 56 ], a conversion that is avoided through the activity of reducing agents such as GSH [ 57 ], glutathione S-transferases [ 58 ] and the duodenal isoform of cytochrome b 561 [ 59 ]. Interestingly, a recent study reported a model regarding the adaptation of RBCs to carry out recycling of intracellular and extracellular AA [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…DHA is an unstable molecule that can be rapidly degraded irreversibly both inside and outside cells [ 56 ], a conversion that is avoided through the activity of reducing agents such as GSH [ 57 ], glutathione S-transferases [ 58 ] and the duodenal isoform of cytochrome b 561 [ 59 ]. Interestingly, a recent study reported a model regarding the adaptation of RBCs to carry out recycling of intracellular and extracellular AA [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…This concept will need to be evaluated in tracing studies with isotope-labeled ascorbate. Alternatively, interspecies divergencies in this pathway may be explained, at least in part, by the evolution of a transport and extracellular reduction system for ascorbate in primates, but not in guinea pigs; this could depend on GLUT1 and Cytochrome B, a membrane-bound cytochrome catalyzing extracellular reduction of Fe 3+ and ascorbate free radical, the first oxidized form of ascorbic acid ( Eigenschink et al, 2021 ). Direct comparison to other rodents is currently missing, though severe storage hemolysis was reported in mice and rats after 14 ( Zimring et al, 2014 ) and 21 days ( Williams et al, 2019 ), respectively, which would preclude examining the 42 day storage period tested here.…”
Section: Discussionmentioning
confidence: 99%
“…In panel A, a minimal conceptual model showing the relationship between glycolysis and glutathione concentration is presented. In panels B1 and B2, experimental data from two independent studies are presented 362,363 . In panel B1, higher glucose levels preserve glutathione concentration after an oxidative insult (2 mM dehydroascorbic acid).…”
Section: The Dynamics Of Erythrocyte Metabolismmentioning
confidence: 99%